Artificial breeding of two geographically separated wild stocks of endangered sarpunti, Puntius sarana (Hamilton) (Bangladesh Journal of Zoology, 2010)
Artificial breeding of Puntius sarana (Hamilton) between and within two different wild stocks, namely Sukhair haor of Sunamgonj districts and Kangsha River of Netrokona district were conducted. Three breeding lines SS (Sukhair x Sukhair), SK (Sukhair × Kangsha) and KK (Kangsha × Kangsha) having three replications of each were tested after breed with pituitary gland extract (6.5mg/kg body weight for female and 2.0mg/kg body weight for male). The highest ovulation (100%), fertilization (84%) and hatching rate (81%) were found in SS followed by SK and KK. The highest length gain (56mm), weight gain (275 mg), SGR (16%) and health condition (4.88 mg/mm) were observed in SK population followed by SS and KK population. The highest survival rate (85%) was also found in SK population and lowest (70%) in KK population.Bangladesh J. Zool. 38(1): 51-59, 2010